Efektivitas Penggunaan Metode Pembelajaran Ekspositori dan Inkuiri dalam Meningkatkan Hasil Belajar Siswa dalam Teks Cerita - Maulida Sari; Prima Nucifera (Universitas Indraprasta PGRI, 2023)
This study aims to describe the comparison of the application of expository learning methods and inquiry learning methods to the ability of students of class VIII on the material element of story formers. The population of the study were students of grade VIII SMPN 4 Kota Langsa which amounted to 204 students spread in nine classes. The sample of research is 43 students of class VIII SMPN 4 Kota Langsa by taking 2 classes that are class VIII-1 and VIII-5. The method used is the experimental method. The research data was collected through the test technique that was processed by using statistical formula. The research design used is Pretest - Posttes Control Design Group. Based on the results of the application of both methods of learning, the use of methods of expository learning and inquiry lerning can improve student learning outcomes. This is evidenced from the result of t-test of Sig value. (2-tailed) by 0.000 <Î± (0.05). From the result of the percentage of pre-test and post-test value, the Class using Expository learning method has increased the learning result by 20% and the inquiry learning class has increased by 26%. Judging from the presentation, the inquiry class is better in improving the learning outcomes of students of grade VIII SMPN 4 Kota Langsa especially on the material of story forming elements.Keywords: expository learning, inquiry learning, student learning outcomes